NEW ADVANCES IN THE DIAGNOSIS AND TREATMENT OF PEDIATRIC MIGRAINE - XIANG Yu, ZHANG Ying, YI Zhi, YANG Chengqing, LI Fei, XUE Jiao, LIU Kaixuan, SONG Zhenfeng (精准医学杂志, 2023)
Migraine is one of the most common disabling neurological diseases in children and seriously affects the physical and mental health of children. The incidence and disability rates of migraine are gradually increasing in recent years, but its pathogenesis remains unclear. This article mainly reviews the clinical manifestations of pediatric migraine and the latest classification and diagnostic criteria, summarizes the pathophysiological mechanism of pediatric migraine and genetic research advances, and discusses the acute treatment, preventive treatment, and latest treatment methods for pediatric migraine.